Universality vs. Cultural Specificity in the Relations Among Emotional Contagion, Emotion Regulation, and Mood State: An Emotion Process Perspective - Kuang, Beibei; Peng, Shenli; Xie, Xiaochun; Hu, Ping (Frontiers in Psychology, 2019)
To investigate the universality and cultural specificity of emotion processing in children from three different ethnic groups (Han, Jingpo, and Dai), we administered three questionnaires, including the emotional contagion scale, emotion regulation scale, and the Chinese mood adjective check list, to 1,362 ethnic Han, Dai, and Jingpo participants (Mage = 13.78 years). Structural equation modeling was used to examine the universality and cultural specificity in the relations among emotional contagion, emotion regulation, and mood state. The results revealed that emotion regulation mediated the relation between emotional contagion and mood state: positive emotional contagion increased positive mood state and decreased negative mood state by the mediated role of reappraisal, negative emotional contagion decreased positive contagion and increased negative mood state by the inconsistent mediated role of reappraisal; negative contagion increased negative mood state by the mediated role of suppression. We found both universality and cultural specificity in the relations among emotional contagion, emotion regulation, and mood state. Regarding cultural specificity, among Dai and Jingpo participants, negative contagion positively predicted reappraisal, while for Han participants, it did not; Jingpo participants demonstrated a weaker negative relation between reappraisal and negative mood state, and a stronger positive relation between negative contagion and suppression; and Dai participants were the only ethnic group that showed a negative connection between negative contagion and positive mood state. Regarding emotion universality, the three ethnic groups all showed positive relations between negative contagion and negative mood, and between suppression and negative mood; additionally, positive contagion positively predicted positive mood state, mediated by reappraisal. Thus, some emotion processes are universal and others more specific. In this paper, we discuss universal emotion processes and ethnic cultural differences in these emotion processes.